Diverse architectures and luminescence properties of two novel copper(i) coordination polymers assembled from 2, 6-bis[3-(pyrid-4-yl)-1, 2, 4-triazolyl]pyridine ligands1. Issue 7 (21st February 2015) - Pan, Jie; Liu, Cai-Ping; Jiang, Fei-Long; Wu, Ming-Yan; Chen, Lian; Qian, Jin-Jie; Su, Kong-Zhao; Wan, Xiu-Yan; Hong, Mao-Chun
<x xml:space="preserve">Abstract</x> Two attractive Cu(i) coordination polymers based on a V-shaped multidentate N-containing ligand H2bptp, have been successfully synthesized.